A method for upgrading polyester materials by degradation of aromatic ester solvents
By using aromatic ester solvents and solid base catalysts in textile waste for depolymerization, the problems of complex separation and low-value recycling in textile recycling are solved, and efficient and economical textile waste upgrade and recycling are achieved.
Patent Information
- Application Number
- CN202411525175.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Existing textile recycling technologies have expensive and complex prebleaching, presorting and separation problems, and it is difficult to effectively upgrade textile waste to high-value chemicals.
In the depolymerization reaction of aromatic ester solvents and solid base catalysts, the polyester fibers in the textile waste are degraded into dicarboxylic acid esters and bisphenyl esters to achieve upgraded recycling of textile waste.
Textile waste can be efficiently recycled without complex pre-decolorization and pre-separation. The target product has high yields, mild reaction conditions and a yield of up to 99%, which helps to improve the economic recyclability of textiles.
Abstract
Description
Technical Field
[0001] The invention relates to an innovative recycling of waste resources and a refined cascade utilization strategy for raw materials, and in particular to a method for upgrading polyester materials by degradation of aromatic ester solvents. Background Art
[0002] Among the necessities of life, clothing ranks first. It not only covers the body and keeps warm, but also reflects the changes in identity and aesthetics. With the rise of fast fashion, the demand for textiles is also growing. According to statistics, global fiber production will increase to 113 million tons in 2023, almost doubling in the past 20 years, and is expected to increase to 149 million tons by 2030.
[0003] Fast fashion consumption has further shortened the life of textiles. According to the National Institute of Standards and Technology (NIST), more than 50 billion pieces of clothing are discarded within one year of production each year. An estimated 92 million tons of textile waste is generated worldwide each year, of which less than 1% is recycled and about three-quarters is landfilled or incinerated, causing huge waste of resources and serious environmental pollution. Greenhouse gas emissions from textiles account for 5-10% of global greenhouse gas emissions, and about one-third or more of the microplastics entering the ocean come from clothing waste. Therefore, it is imperative to develop sustainable and environmentally friendly textile recycling technologies.
[0004] At present, textiles are mainly divided into two categories: natural textiles and synthetic textiles. While the production of plant and animal raw materials (such as cotton and wool) is relatively stable, the output of synthetic textiles is growing rapidly. The most widely used synthetic fiber is PET, which will account for 54% of the global fiber production by 2021. The most direct way to recycle waste PET is to use it as fuel energy. However, burning plastics will release a lot of toxic gases and produce a lot of carbon emissions, which runs counter to the sustainable development concept of low carbon emissions.
[0005] In addition, mechanical recycling is also the most commonly used method for recycling colored textiles, but for multi-fiber textiles, improper handling of additives and colorants often leads to shortened fiber length, damaged toughness, strength and creep resistance, and can only be recycled as low-value products such as wipes, fillings and insulation materials.
[0006] Chemical recycling technologies have attracted much attention and have been extensively studied. However, polyester fibers in textiles are often closely intertwined with other fibers (including cotton, nylon, and spandex) and various dyes. Therefore, chemical recycling of mixed textile waste usually requires expensive sorting and separation before reprocessing to avoid unwanted product mixing. For example, Zuo et al. established a new closed-loop strategy to recycle waste polyester textiles by developing multiple technologies, including decolorization of waste textiles, glycolysis of decolorized polyester textiles, and purification of BHET products. However, the remaining unreacted other waste textiles were not processed ( Green Chem., 2023, 25 (11), 4429-4437). Based on this, Vlachos et al. used microwave-assisted glycolysis to recover polyester, cotton, nylon and spandex from mixed textile waste. Although no pre-bleaching and pre-sorting were required, polyester and spandex were completely degraded within 15 minutes, while cotton and nylon were completely retained, but polyester was only degraded to monomers, and no upgraded products were obtained ( Sci. Adv., 2024, 10 (27), eado6827).
[0007] Therefore, developing sustainable recycling technologies for complex mixed textile waste (especially polyester cotton, which is an interwoven mixture of polyester and cotton), solving the current expensive and complex pre-bleaching, pre-sorting and separation problems, and effectively upgrading textile waste into high-value chemicals are new directions and new challenges for achieving a comprehensive green transformation of the textile industry. Summary of the invention
[0008] The present invention aims at the problems of expensive and complicated pre-bleaching, pre-sorting and separation and single product upgrading in the degradation of textile waste, and provides a method for upgrading polyester materials by using aromatic ester solvents. The method can realize the upgrading and recycling of textile waste without complicated pre-bleaching and pre-separation, and the yield of the target product is high.
[0009] A method for upgrading polyester materials by degradation of aromatic ester solvents comprises the following steps:
[0010] A polyester material, an aromatic ester solvent and a solid base catalyst are placed in a reaction kettle and heated to perform a depolymerization reaction to obtain a dicarboxylic acid ester and a diphenyl ester, wherein the aromatic ester solvent is at least one of methyl benzoate, p-methyl benzoate, methyl phenylacetate, ethyl benzoate, m-methyl benzoate, o-methyl benzoate, methyl phenylpropionate, allyl benzoate, ethyl p-methyl benzoate, ethyl o-methyl benzoate or ethyl m-methyl benzoate, and the solid base catalyst is at least one of zinc oxide, magnesium oxide, cadmium oxide, zinc hydroxide or cadmium hydroxide.
[0011] Preferably, the polyester material is textile waste containing polyethylene terephthalate (PET).
[0012] Polyester fibers made of PET are usually tightly interwoven with other fibers (synthetic or natural polymers) such as cotton, nylon, spandex, dyes, etc., and require expensive sorting and separation (such as high temperature and long-term decolorization treatment) before reprocessing. According to the principle of "like dissolves like", the present invention uses aromatic ester solvents with good solubility in textile waste containing polyester fibers, which can directly dissolve and peel PET from tightly interwoven complex textiles, and depolymerize polyester fibers into dicarboxylic acid esters through ester exchange reaction; in addition, the present invention can effectively reduce the activation energy of the reaction by introducing a solid base catalyst, so that the reaction can be carried out at a lower temperature, making the reaction conditions milder and more controllable, and the selectivity and yield of the target product higher.
[0013] Preferably, the textile waste containing polyethylene terephthalate includes at least one of polyester fabric, cotton blended fabric, polyester fiber, PU blended fabric, rayon blended fabric, etc. For example, it can be polyester fabric, polyester-cotton blended fabric, polyester fiber-PU blended fabric and polyester fiber-rayon blended fabric. Further preferably, the textile waste containing polyethylene terephthalate is discarded colored textile waste containing polyethylene terephthalate. The present invention utilizes the solubility of aromatic ester solvents in PET to efficiently peel off PET tightly interwoven with impurities, thereby avoiding expensive sorting and separation in the early stage, and further improving the purity of the product.
[0014] Preferably, the mass proportion of polyethylene terephthalate in the polyethylene terephthalate-containing textile waste is 40-100%. The proportion of polyester in most polyester-containing textile waste on the market is within this range.
[0015] The method of the present invention can also be applied to waste materials containing other similar polyesters. For example, the polyester material is waste materials containing polybutylene terephthalate, including cloth, computer keycaps, fuse boxes, switches, sockets or electronic component brackets containing the material.
[0016] Preferably, the polyester material needs to be pre-crushed into cm-level flakes, granules or powders before being added to the reactor to ensure the resource utilization effect of the polyester material and to obtain the dicarboxylic acid ester monomer in a targeted manner with high yield.
[0017] Preferably, 2 to 8 mL of aromatic ester solvent is added per mmol of polyester material. Further preferably, 4 to 6 mL of aromatic ester solvent is added per mmol of polyester material. More preferably, 5 mL of aromatic ester solvent is added per mmol of polyester material. Within this control range, the yield of the reaction product is the highest and the amount of aromatic ester solvent used is the lowest.
[0018] Preferably, the amount of the solid base catalyst added is 20-80 mol% of the polyester material. Further preferably, the amount of the solid base catalyst added is 20-50 mol% of the polyester material. Within this range, the reaction time can be shortened and the product yield can be maximized.
[0019] Preferably, the reaction temperature of the depolymerization reaction is 160-240° C., and the reaction time is 5-16 hours. More preferably, the reaction temperature of the depolymerization reaction is 180-220° C. More preferably, the reaction temperature of the depolymerization reaction is 200° C.
[0020] Preferably, the aromatic ester solvent is methyl benzoate, and the polyester material is textile waste containing polyethylene terephthalate. Methyl benzoate is a natural aromatic ester compound that can be extracted from natural essential oils such as clove oil. A solid base catalyst is used to catalyze the transesterification reaction between methyl benzoate and a blended product containing PET, PET is degraded into dimethyl terephthalate (DMT), and methyl benzoate captures the ethylene glycol unit in PET and is upgraded to high-value diethylene glycol dibenzoate (EGD).
[0021] In the present invention, methyl benzoate is used to improve the solubility of PET in the solvent, leaving waste residues other than PET in the textile waste; on the other hand, methyl benzoate can also be used as a capture agent for EGD produced by PET depolymerization, and the product DMT is obtained through ester exchange reaction, while high-value ethylene glycol dibenzoate (EGD) is co-produced, thereby improving the economic efficiency of atomic utilization.
[0022] DMT is an important bulk chemical with broad application prospects in the construction, packaging, electronics and other industries. EGD, as an important synthetic intermediate, is widely used in the preparation of coatings, fragrances and plastic additives. This new strategy for degrading PET-containing waste textiles will help improve the economic efficiency of textile recycling and promote the comprehensive green transformation of the textile industry.
[0023] Preferably, the aromatic ester solvent is methyl benzoate, the polyester material is textile waste containing polyethylene terephthalate, the solid base catalyst is zinc oxide, the reaction temperature is 180-220°C, and the reaction time is 10-15h. More preferably, the reaction temperature is 200°C, and the reaction time is 12h. Under these conditions, the yield of the target product dimethyl phthalate can be as high as 99%, and the yield of diethylene glycol dibenzoate can be as high as 85%.
[0024] The present invention can also use other aromatic esters with similar structures as solvents, such as methyl p-toluate, ethyl benzoate, allyl benzoate, etc., and the products are corresponding dimethyl terephthalate, diethyl terephthalate, diallyl terephthalate and diphenyl ester, etc.
[0025] Compared with the prior art, the present invention has at least the following beneficial effects:
[0026] (1) The aromatic ester and solid base catalyst system used in the present invention has good solubility for polyester materials, and can achieve the upcycling of difficult-to-treat colored textile waste without complicated pre-decolorization and pre-separation;
[0027] (2) The aromatic ester degradation and upgrading strategy for textile waste developed in the present invention has the advantages of mild reaction conditions and high catalytic efficiency. It can achieve complete conversion of PET under standard reaction conditions without the need for a high-pressure environment and can complete depolymerization under normal pressure. The yield of the prepared dicarboxylic acid ester is as high as 99%, and the yield of diphenyl ester is as high as 85%, which helps to improve the economic recyclability of textiles and promote the comprehensive green transformation of the textile industry.
[0028] (3) The present invention can use a variety of aromatic ester solvents, such as p-methylbenzoate, methyl phenylacetate, ethyl benzoate, allyl benzoate, etc., and can also use other similar aromatic ester solvents to degrade the polyester-containing material to obtain different transesterification products, thereby broadening the range of products;
[0029] (4) The method of the present invention has a wide range of applicability. For example, textile waste containing PET can be replaced by other materials containing similar polyesters such as polybutylene terephthalate, further broadening the scope of the polyester materials that can be processed. DETAILED DESCRIPTION
[0030] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, a detailed description is given below through specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.
[0031] The present invention provides a method for degrading and upgrading textile waste using aromatic ester solvents. The method uses aromatic esters and PET to undergo an ester exchange reaction under the catalytic action of a solid base, wherein PET is degraded into monomer DMT, and the aromatic ester captures ethylene glycol and then dehydrates and condenses into diphenyl ester. The specific steps of the method are as follows:
[0032] S1, placing crushed textile waste, aromatic ester raw materials, and solid base catalyst in a reaction kettle to form a reaction system;
[0033] S2, placing the reactor containing the reaction system at a depolymerization temperature of 160-240° C. for 5-16 h of depolymerization reaction, and cooling to room temperature after the reaction is completed to obtain a depolymerization product containing dicarboxylic acid ester and diphenyl ester.
[0034] In the subsequent examples, the raw materials in the above reaction system are as follows:
[0035] The polyester materials are materials containing polyethylene terephthalate and polybutylene terephthalate; the aromatic ester raw materials are methyl benzoate, methyl p-toluate, ethyl benzoate, and allyl benzoate; and the solid base catalysts are zinc oxide, magnesium oxide, and cadmium oxide.
[0036] If the polyester material is PET, pure PET or PET waste can be used. The waste form is that the polyester material is complex waste colored PET, such as polyester fabric, polyester-cotton blended fabric, polyester-PU blended fabric and polyester-rayon blended fabric; if the polyester material is polybutylene terephthalate, the selected materials are fabric, computer keycaps, fuse boxes, switches and sockets or electronic component brackets of this material. However, the waste needs to be pre-crushed into cm-level flakes, particles or powders before adding to the reactor.
[0037] The following examples are used to demonstrate the reaction results under different raw materials and parameters. Example 1
[0038] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material, methyl benzoate (2, 5, 8 mL / mmol polyester material) and ZnO (35mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yields of dimethyl terephthalate were 92%, 99%, and 95%, respectively, and the yields of diethylene glycol dibenzoate were 82%, 85%, and 83%, respectively. Example 2
[0039] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material, 5 mL of methyl benzoate (5 mL / mmol polyester material) and ZnO (20 mol%, 35 mol%, 50 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yields of dimethyl terephthalate were 92%, 99%, and 97%, respectively, and the yields of diethylene glycol dibenzoate were 82%, 85%, and 85%, respectively. Example 3
[0040] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material, 5 mL of methyl benzoate (5 mL / mmol polyester material) and ZnO (35mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 180, 200, and 220 ° C, respectively, and reacted at this temperature for 12 h. After the reaction was completed, it was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yields of dimethyl terephthalate were 91%, 99%, and 96%, respectively, and the yields of diethylene glycol dibenzoate were 81%, 85%, and 83%, respectively. Example 4
[0041] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material, 5 mL of methyl benzoate (5 mL / mmol polyester material) and ZnO (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 8, 12, and 16 h, respectively. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yields of dimethyl terephthalate were 90%, 99%, and 97%, respectively, and the yields of diethylene glycol dibenzoate were 77%, 85%, and 83%, respectively. Example 5
[0042] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material and 5 mL of methyl benzoate (5 mL / mmol polyester material) were added. ZnO, MgO, and CdO (35 mol%) were used as catalysts, respectively. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yields of dimethyl terephthalate were 99%, 99%, and 99%, respectively, and the yields of diethylene glycol dibenzoate were 85%, 84%, and 85%, respectively. Example 6
[0043] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of 80% polyester-20% cotton blended fabric, 5 mL of methyl benzoate (5 mL / mmol polyester material) and ZnO (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of diethylene glycol dibenzoate was 85%. Example 7
[0044] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of 95% polyester fiber-3% PU blended fabric, 5 mL of methyl benzoate (5 mL / mmol polyester material) and ZnO (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of diethylene glycol dibenzoate was 84%. Example 8
[0045] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of 40% polyester fiber-60% rayon blended fabric, 5 mL of methyl benzoate (5 mL / mmol polyester material) and ZnO (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200°C and reacted at this temperature for 12 h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured for yield by GC, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yield of dimethyl terephthalate was 99%, and the yield of diethylene glycol dibenzoate was 85%. Example 9
[0046] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material, 5 mL of ethyl benzoate (5 mL / mmol polyester material) and ZnO (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 hours. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yield of diethyl terephthalate was 97%, and the yield of diethylene glycol dibenzoate was 84%. Example 10
[0047] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material, 5 mL of methyl phenylpropionate (5 mL / mmol polyester material) and ZnO (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 hours. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yield of dimethyl terephthalate was 98%, and the yield of diethylene glycol diphenylpropionate was 83%. Embodiment 11
[0048] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.256 g of computer keycap cm-level crushed material (1 mmol) made of polybutylene terephthalate, 5 mL of methyl benzoate (5 mL / mmol polyester material) and CdO (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 h. After the reaction was completed, it was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with mesitylene as the internal standard. The results showed that the PET degradation rate of this embodiment was 100%, the yield of dibutyl terephthalate was 95%, and the yield of diethylene glycol dibenzoate was 84%. Comparative Example 1
[0049] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-scale crushed material of pure polyester (1 mmol), 5 mL of methyl benzoate (5 mL / mmol of polyester material), and Cu(OH) 2 (35mol%), after placing the autoclave reactor, start stirring and heating. The reaction system is heated to 200 ° C and reacted at this temperature for 12 h. After the reaction is completed, the temperature is cooled to room temperature, and the resulting mixed solution is the product. The resulting mixed solution is diluted with dichloromethane, and the diluent is measured by GC for yield, with mesitylene as the internal standard. The results show that the yield of dimethyl terephthalate in this example is 0%, and the yield of diethylene glycol dibenzoate is 0%. Comparative Example 2
[0050] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-scale crushed material of pure polyester (1 mmol), 5 mL of methyl benzoate (5 mL / mmol of polyester material), and K 2 CO 3 (35mol%), after placing the autoclave reactor, start stirring and heating. The reaction system is heated to 200 ° C and reacted at this temperature for 12 h. After the reaction is completed, the temperature is cooled to room temperature, and the resulting mixed solution is the product. The resulting mixed solution is diluted with dichloromethane, and the diluent is measured by GC for yield, with mesitylene as the internal standard. The results show that the yield of dimethyl terephthalate in this example is 0%, and the yield of diethylene glycol dibenzoate is 0%. Comparative Example 3
[0051] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-scale crushed material of pure polyester (1 mmol), 5 mL of methyl benzoate (5 mL / mmol of polyester material), and Ca(OH)2 (35mol%), after placing the autoclave reactor, start stirring and heating. The reaction system is heated to 200 ° C and reacted at this temperature for 12 h. After the reaction is completed, the temperature is cooled to room temperature, and the resulting mixed solution is the product. The resulting mixed solution is diluted with dichloromethane, and the diluent is measured by GC for yield, with mesitylene as the internal standard. The results show that the yield of dimethyl terephthalate in this example is 3%, and the yield of diethylene glycol dibenzoate is 0%. Comparative Example 4
[0052] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material, 5 mL of methyl benzoate (5 mL / mmol polyester material) and H-ZSM-5 molecular sieve (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with mesitylene as the internal standard. The results showed that the yield of dimethyl terephthalate in this example was 0%, and the yield of diethylene glycol dibenzoate was 0%. Comparative Example 5
[0053] In an autoclave reactor equipped with an electromagnetic stirrer, a thermocouple, and a programmable temperature controller, 0.192 g of cm-level crushed material (1 mmol) of pure polyester material, 5 mL of methyl benzoate (5 mL / mmol polyester material) and Amberlyst 15 (35 mol%) were added. After the autoclave reactor was placed, stirring and heating were turned on. The reaction system was heated to 200 ° C and reacted at this temperature for 12 h. After the reaction was completed, the temperature was cooled to room temperature, and the resulting mixed solution was the product. The resulting mixed solution was diluted with dichloromethane, and the diluent was measured by GC for yield, with mesitylene as the internal standard. The results showed that the yield of dimethyl terephthalate in this example was 0%, and the yield of diethylene glycol dibenzoate was 0%.
[0054] The above Examples 1 to 11 and Comparative Examples 1 to 5 show that not all catalysts can be used to catalyze the above depolymerization reaction. Compared with other catalysts, ZnO, MgO and CdO have extremely high catalytic performance in catalyzing the upgrading of aromatic esters and colored textile wastes to carboxylic esters and diphenyl esters.
[0055] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for upgrading polyester materials by degradation of aromatic ester solvents, characterized in that: The following steps are involved: A polyester material, an aromatic ester solvent and a solid base catalyst are placed in a reaction kettle and heated to perform a depolymerization reaction to obtain a dicarboxylic acid ester and a diphenyl ester, wherein the aromatic ester solvent is at least one of methyl benzoate, p-methyl benzoate, methyl phenylacetate, ethyl benzoate, m-methyl benzoate, o-methyl benzoate, methyl phenylpropionate or allyl benzoate, and the solid base catalyst is at least one of zinc oxide, magnesium oxide, cadmium oxide, zinc hydroxide or cadmium hydroxide.
2. The method according to claim 1, characterized in that The polyester material is textile waste containing polyethylene terephthalate or waste containing polybutylene terephthalate.
3. The method according to claim 2, characterized in that The textile waste containing polyethylene terephthalate includes at least one of polyester fabric, cotton blended fabric, polyester fiber, PU blended fabric, and rayon blended fabric.
4. The method according to claim 3, characterized in that The mass proportion of polyethylene terephthalate in the polyethylene terephthalate-containing textile waste is 40-100%.
5. The method according to claim 1, characterized in that Add 2-8 mL of aromatic ester solvent to every mmol of polyester material.
6. The method according to claim 1, characterized in that The added amount of the solid base catalyst is 20-80 mol% of the polyester material.
7. The method according to claim 1, characterized in that The reaction temperature of the depolymerization reaction is 160-240° C., and the reaction time is 5-16 hours.
8. The method according to any one of claims 1 to 7, characterized in that 4-6 mL of aromatic ester solvent is added to each mmol of polyester material; the amount of the solid base catalyst added is 20-50 mol% of the polyester material; and the reaction temperature of the depolymerization reaction is 180-220°C.
9. The method according to any one of claims 1 to 7, characterized in that: The aromatic ester solvent is methyl benzoate, the polyester material is textile waste containing polyethylene terephthalate, the dicarboxylic acid ester is dimethyl terephthalate, and the diphenyl ester is diethylene glycol dibenzoate.
10. The method according to claim 9, characterized in that The solid base catalyst is zinc oxide, the reaction temperature is 180-220° C., and the reaction time is 10-15 hours.
Citation Information
Patent Citations
Preparation of monomer terephthalaciddiester-and-diol from polyester
CN1086206A
Method for recovering polyester from contaminated polyester waste
CN1252823A